Menopause education of healthcare professionals: A scoping review protocol - C. Keye; Murphy M; Saab MM; O’ Driscoll M (PLoS ONE, 2025)
The reported lack of adequate menopause care is a significant issue, leaving many women feeling isolated and unsupported as they navigate this transition. The increasing mainstream attention on menopause healthcare highlights the need to evaluate whether healthcare professionals are adequately educated and competent to provide effective care for menopausal women. The aim of this scoping review is to ascertain to what extent undergraduate and post registration healthcare professionals are educated regarding menopause throughout their training and subsequent careers, with a view to informing future educational initiatives. This scoping review will be carried out using the JBI Manual for Evidence Synthesis and reported using the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for scoping reviews checklist. It will include all healthcare professionals relevant to the provision of menopause care, including medical doctors, nurses, midwives, pharmacists, physiotherapists, and psychologists. The search will use the following databases: CINAHL; MEDLINE; EMBASE; APA PsycINFO; ERIC; and Academic Search Complete. Grey literature will be searched using Google Scholar and Open Grey. An academic librarian has been contacted to assist in the development of the search strategy. Covidence online software will be used to manage the screening and data extraction process. Purposely developed data extraction tables will be created by the reviewers. The data will be synthesised and reported narratively.